The Effect of Back Swing and Foreward Swing Toward Forehand Drive Performance on Tennis Learning - Masrun Masrun; Alnedral Alnedral; Damrah Damrah (Universitas PGRI Palembang, 2022)
The problem of the research was student’s lack forehand drive ability that resulting less points obtained while playing or hitting the ball. This research aimed to identify factors that causally and positively effecting the student’s forehand drive performance, namely back swing and forward swing phases. This study involved 31 male student’s who learning tennis subject in Sport Science Faculty, Padang State University. The samples tested using Broer-Miller-Tennis Test, and observed by judge. The data was analyzed by using Regression Analysis utilizing IBM SPSS software. To find out the causal factors which independently and dependently influence each variable, it is used the significance level <0.05 The results shos that Backswing had significant and positive effect on the accuracy of the forehand drive (p <0.05) . The significance level was p <0.05 or H0 was rejected. Furthermore, Forwardswing had significant and positive effect on the accuracy of the forehand drive (p <0.05) or H0 is rejected. The results of the study show that there is a positive causal effect of backswing and forwardswing on athlete's forehand drive performance.